Analytical Calculation of Air-gap Magnetic Field and Torque of Triple-shaft Ring-plate Magnet Gears - Liu Dongning; Ge Yanjun; Yang Junyue; Wang Daming (Jixie chuandong)
In this research, the mathematical and physical model of the air-gap magnetic field for the triple-shaft ring-plate magnet gear (TRMG) is obtained by means of the scalar magnetic potential method, and the air-gap magnetic field between inner and outer permanent magnet rings and its corresponding electromagnetic torque model are established according to the principle of the magnetic field superposition. Since all calculations are based on the TRMG plane magnetic field, the accuracy between the model and the two-dimensional finite element results is relatively high (error≤5%). The calculation speed of the model is much faster than that of the three-dimensional finite element method, and it has good agreement and trend with the two-dimensional and three-dimensional finite element analysis, which verifies the correctness of the model. It can be used in magnetic field analysis and structural dynamics calculation of multishaft ring-plate magnet gears with three or more shafts.